Controller Design and Disturbance Rejection of Multi-Quadcopters for Cable Suspended Payload Transportation Using Virtual Structure - Xiao Han; Ryo Miyazaki; Tianhua Gao; Kohji Tomita; Akiya Kamimura (IEEE Access, 2022)
Quadcopter is a type of unmanned aerial vehicle (UAV) that offers excellent flight ability albeit with relatively low payload. Despite its widespread use for transportation, improving its robustness against disturbances and carrying capacity has been challenging. Thus, this study proposed a cable suspended multi-UAVs transportation system with a controller and disturbance observer that is highly robust against disturbances. The primary objective of this study is to design a robust controller and disturbance observer by considering the effect of the cable-suspended payload on the UAV as a part of the disturbance. Consequently, reducing the complexity of the problem and allowing a range of algorithms to be used. A controller and disturbance observer are designed based on backstepping control and the extended state of the model, respectively, to control the flight of the multiple UAVs while carrying a cable-suspended payload. Further, to exploit the agility of quadcopters and avoid obstacles, a virtual structure based leader-follower dynamic formation scheme is introduced to change the formation geometry during the flight with cable suspended payload. This scheme does not make any assumption regarding the status of cable tension during the flight and thus no feedback measurement is required from payload. Moreover, the stability analysis of the proposed system is verified theoretically based on Lyapunov stability and through indoor experiments.